Representation of Psychological Impact in the Film Melukis Luka (Charles Sanders Pierce's Semiotics) - Zidan Rahmatullah; Didi Permadi; Ike Desi Florina (Sean Institute, 2025)
This study aims to analyze how the film Melukis Luka represents the psychological impact experienced by ethnic Chinese survivors of the May 1998 tragedy through Charles Sanders Peirce's semiotic approach. The research method uses a descriptive qualitative approach with documentation techniques and sign analysis consisting of signs, objects, and interpretants in the film's scenes. The results of the study indicate that the film Melukis Luka represents four main forms of psychological impact, namely post-traumatic stress disorder (PTSD), excessive anxiety, personality disorders, and difficulties in regulating emotions and behavior. These impacts are depicted through the traumatic experiences of the character Hanry such as nightmares, fear of crowds, withdrawal behavior, and wariness of strangers as a response to the loss of family during the riots. This study concludes that Melukis Luka functions not only as a medium of entertainment, but also as a space for historical reflection and social criticism of the long-term impact of the May 1998 tragedy that is still felt today. Thus, Melukis Luka presents a humanitarian narrative that invites the audience to not forget history and build empathy for survivors who continue to struggle to face their wounds.